Abstract 4284: Exploratory plasma proteomic analysis in a randomized cross-over trial of aspirin among healthy individuals - Wang, Xiaoliang; Zhang, Yuzheng; Shojaie, Ali; Lampe, Paul D.; Levy, Lisa; Peters, Ulrike; Potter, John D.; White, Emily; Lampe, Johanna W. (Cancer research (Chicago, Ill.), 2016)
Background: Long-term use of aspirin is associated with lower colorectal cancer (CRC) incidence; however, the mechanism of the chemopreventive effect of aspirin is not fully understood. Animal studies suggest that COX-2, NFκB signaling and Wnt/β-catenin pathways may play a role, but no clinical trials have systematically evaluated the biological response to aspirin in healthy humans. Methods: We assessed the difference in plasma protein levels after 60 days of regular dose aspirin (325 mg/day) compared to placebo in a randomized, double-blinded, placebo-controlled, cross-over trial of 44 healthy non-smoking men and women, aged 21-45 years. Plasma proteomics was analyzed on an antibody microarray with ∼3,000 full-length antibodies, printed in triplicate. Moderated paired t-test was performed on individual antibodies, and gene set analyses were performed for KEGG and GO pathways. Results: Among the 3,387 antibodies, significant differences in plasma protein levels were observed for 267 antibodies (p<0.05), the most significant protein being a transcription-factor regulator belonging to a steroid receptor family and found to be differentially expressed in colon cancer cells. Other significant proteins are involved in multiple oncogenic pathways related to colon tumorigenesis. In the pathway analysis, 4 KEGG (among 138) and 69 GO (among 1,089) pathways were found to be significant (p<0.05), including natural killer (NK) cell-mediated cytotoxicity, butanoate metabolism and Wnt signaling pathways. Pathways that modulate cellular protein binding to steroid receptors were also significantly different between aspirin treatment and placebo (p<0.05). None of the results remained statistically significant after correction for multiple testing. Conclusion: Several proteins and pathways, which have previously been reported as playing a role in colorectal carcinogenesis in vitro were found to be differentially expressed after aspirin treatment vs. placebo in healthy human subjects. This study suggests several chemopreventive mechanisms of aspirin; however, larger, confirmatory studies are needed. Citation Format: Xiaoliang Wang, Yuzheng Zhang, Ali Shojaie, Paul D. Lampe, Lisa Levy, Ulrike Peters, John D. Potter, Emily White, Johanna W. Lampe. Exploratory plasma proteomic analysis in a randomized cross-over trial of aspirin among healthy individuals. [abstract]. In: Proceedings of the 107th Annual Meeting of the American Association for Cancer Research; 2016 Apr 16-20; New Orleans, LA. Philadelphia (PA): AACR; Cancer Res 2016;76(14 Suppl):Abstract nr 4284.